SISTEM INFORMASI PEMBELAJARAN JARAK JAUH BERBASIS WEB PADA SDN 04 AIR PURA - Putri Ramadani; Maisan Dewi Puspa Khairani; Desi Irfan; Nur Aini (Smart Education, 2026)
Abstract: The rapid digital transformation in Indonesian primary education has shifted from an emergency response to a long-term structural necessity. However, primary schools in areas with limited infrastructure, such as UPT SDN 04 Air Pura, still face significant challenges regarding the digital divide and the lack of integrated information systems. This research aims to design and implement a web-based Distance Learning Information System to bridge the gap between academic administration and online learning delivery. Applying the Waterfall development method, this system integrates features for managing student data, attendance, assignments, and digital grade reports within a single platform. Built using PHP, MySQL, and the CodeIgniter framework, the system provides an efficient, accurate, and accessible solution for teachers, students, and school administrators. Black box testing confirms that the system functions fully and effectively, offering a viable solution for sustainable distance learning and improving digital education equity in regions with limited telecommunications infrastructure. Keywords: Distance Learning, Information System, Web-Based, Primary Education, Waterfall Abstrak: Transformasi digital dalam pendidikan dasar di Indonesia telah menjadi kebutuhan struktural jangka panjang. Namun, sekolah dasar di wilayah dengan keterbatasan infrastruktur, seperti UPT SDN 04 Air Pura, masih menghadapi tantangan kesenjangan digital dan ketiadaan sistem informasi terintegrasi. Penelitian ini bertujuan untuk merancang dan membangun Sistem Informasi Pembelajaran Jarak Jauh berbasis web guna mengintegrasikan administrasi akademik dan penyampaian materi pembelajaran. Dengan menerapkan metode pengembangan Waterfall, sistem ini mengintegrasikan fitur manajemen data siswa, absensi, tugas, dan raport digital dalam satu platform. Aplikasi yang dibangun menggunakan bahasa pemrograman PHP, basis data MySQL, dan framework CodeIgniter ini terbukti mampu menyediakan solusi yang efisien, akurat, serta mudah diakses bagi guru dan siswa. Hasil pengujian black box menunjukkan bahwa sistem berfungsi secara optimal dan siap mendukung keberlanjutan pembelajaran jarak jauh, sekaligus berkontribusi terhadap pemerataan akses pendidikan digital di tingkat sekolah dasar dengan infrastruktur terbatas. Kata kunci: Pembelajaran Jarak Jauh, Sistem Informasi, Berbasis Web, Pendidikan Dasar, Waterfall